2009
DOI: 10.1289/ehp.0800029
|View full text |Cite
|
Sign up to set email alerts
|

Activated Toxicity of Diesel Particulate Extract by Ultraviolet A Radiation in Mammalian Cells: Role of Singlet Oxygen

Abstract: BackgroundDiesel exhaust [diesel exhaust particles (DEPs) and their extracts (DPE)] and ultraviolet A radiation (UVA) are two ubiquitous environmental factors that have been identified as essential risk factors for various benign or malignant human diseases, either alone or in combination with other agents.ObjectivesWe aimed to investigate the synergistic effects of DPE and UVA at low-dose exposures in human–hamster hybrid (AL) cells and their underlying mechanisms.MethodsWe exposed exponentially growing AL ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 68 publications
3
30
0
Order By: Relevance
“…However, to specifically reveal the potential carcinogenic effects of PAHs, application of organic extracts is more relevant. Although the genotoxicity of DEP extracts may be easily tested by standardized, well-established tests including cytotoxicity measurement [20], Ames test [20,21], analysis of double strand DNA breaks [21], apoptosis, frequency of micronuclei [22], bulky DNA adducts formation or oxidative DNA damage [12], for a comprehensive assessment of the biological processes induced by the DEP extracts the treatment of the whole genome gene expression analysis is a valuable tool.…”
Section: Introductionmentioning
confidence: 99%
“…However, to specifically reveal the potential carcinogenic effects of PAHs, application of organic extracts is more relevant. Although the genotoxicity of DEP extracts may be easily tested by standardized, well-established tests including cytotoxicity measurement [20], Ames test [20,21], analysis of double strand DNA breaks [21], apoptosis, frequency of micronuclei [22], bulky DNA adducts formation or oxidative DNA damage [12], for a comprehensive assessment of the biological processes induced by the DEP extracts the treatment of the whole genome gene expression analysis is a valuable tool.…”
Section: Introductionmentioning
confidence: 99%
“…16 As shown in Figure 8D and E, 4-O-TEMPO triplet spectra and the relative signal intensity increased considerably in worms coexposed to DPE (20 μg/mL) plus UVA (0.5 J/cm 2 ) compared with those in the single treatment of DPE or UVA, or with the control worms, and NaN 3 (100 μM) significantly reduced this signal ( P < 0.05). Taken together, the results indicated that the ROS, especially 1 O 2 , played a pivotal role in the induction of germ cell apoptosis within C. elegans by coexposure to DPE plus UVA.…”
Section: Resultsmentioning
confidence: 78%
“…1 O 2 was distinctly detected as shown in Figure 5, and addition of NaN 3 to the medium concentration-dependently reduced formation of singlet oxygen ( Figure 6). Some investigators also reported generation of singlet oxygen induced in the presence of several photosensitizers following UV-A irradiation (Yin et al 2008;Bao et al 2009;Zhang et al 2011). Some nutrients also act as photosensitizers as noted by several investigators (for example, vitamins (riboflavin), porphyrins, nicotinamide (Baier et al 2006;Carbonare and Pathak 1992), lipids, free fatty acids (Regensburger et al 2012)).…”
Section: Discussionmentioning
confidence: 87%
“…ROS were induced by UV photo-irradiation of some photosensitizers in a medium containing fatty acids and vitamins (Regensburger et al 2012) and cytoplasmic urocanic acid, riboflavin, and b-nicotinamide adenine dinucleotide (NAD) (Baier et al 2006). Moreover, harmful chemical compounds such as crude coal tar, benzo[a]pyrene (Crallan, Ingham, and Routledge 2005), and diesel exhaust particles (Bao et al 2009;Guo et al 2014) also induced ROS associated with UV irradiation. However, some scavengers, such as glutathione (GSH), catalase (CAT), N-acetylcysteine (NAC), superoxide dismutase (SOD), and vitamin C, are contained in the cells or medium.…”
mentioning
confidence: 99%